Polska w rozszerzonej Unii Europejskiej - Dobroczyński, Michał (Poland in the Enlarged European Union, 2005)
A number of particular economic, political and social features creates polish strong national identity, which largely differs from those of the majority of EU member states. Predominantly due to historical factors, but to some present structural aspects as well. Poland belongs to less developed economies of the Union, but by its size should be considered as one of the top EU subjects. So it can be expected that in predominantly favourable circumstances the country will be in position to rationally integrate with the twenty four close partners. Despite several difficult barriers of economic and socio-psychological nature.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 51-61